The Omicron variant is highly resistant against antibody-mediated neutralization: Implications for control of the COVID-19 pandemic - Hoffmann, Markus; Krüger, Nadine; Schulz, Sebastian; Cossmann, Anne; Rocha, Cheila; Kempf, Amy; Nehlmeier, Inga; Graichen, Luise; Moldenhauer, Anna Sophie; Winkler, Martin S.; Lier, Martin; Dopfer-Jablonka, Alexandra; et al. (Cell, 2022)
The rapid spread of the SARS-CoV-2 Omicron variant suggests that the virus might become globally dominant. Further, the high number of mutations in the viral spike protein raised concerns that the virus might evade antibodies induced by infection or vaccination. Here, we report that the Omicron spike was resistant against most therapeutic antibodies but remained susceptible to inhibition by sotrovimab. Similarly, the Omicron spike evaded neutralization by antibodies from convalescent patients or individuals vaccinated with the BioNTech-Pfizer vaccine (BNT162b2) with 12- to 44-fold higher efficiency than the spike of the Delta variant. Neutralization of the Omicron spike by antibodies induced upon heterologous ChAdOx1 (Astra Zeneca-Oxford)/BNT162b2 vaccination or vaccination with three doses of BNT162b2 was more efficient, but the Omicron spike still evaded neutralization more efficiently than the Delta spike. These findings indicate that most therapeutic antibodies will be ineffective against the Omicron variant and that double immunization with BNT162b2 might not adequately protect against severe disease induced by this variant.
CRIS-Team Scopus Importer:2022-01-28
Keywords: antibody; immune evasion; neutralization; Omicron; SARS-CoV-2; spike; vaccine